Body lipid deposition in Nile tilapia fed on rations containing tannin - Aiura, Felipe Shindy; Carvalho, Maria Regina Barbieri de (Pesquisa Agropecuaria Brasileira, 2007)
The aim of this work was to evaluate the effect of tannin sources and levels in rations, on the productive performance and body lipid deposition of Nile tilapias (Oreochromis niloticus) during the finishing phase. Three hundred and forty-two fishes were distributed in 18 tanks. Rations were prepared using corn, sorghum varieties, with low and high tannin content, and tannic acid at 0.08, 0.34, and 0.60%. Weight gain, apparent feed conversion and protein efficiency rate were not influenced by the treatments. The highest body lipid deposition was observed for the tannic acid treatment (14.39%), while the diet containing sorghum with high tannin content yielded leaner body (12.01%) than that of sorghum with low tannin content (13.31%). Diets containing sorghum provided lower levels of visceral fat. Rations with tannin contents did not harm the productive performance of Nile tilapia.